GSM based traffic light fault reporting system - Randeni, Tinashe (Midlands State University, 2017)
Traffic signal breakdowns are a common problem in the CBD areas of cities and towns. When these breakdowns occur, unsafe road conditions for motorists and pedestrians emerge whereby there is chaos at intersections with each driver trying to proceed without considering other motorists. This leads to traffic jams, delays and collisions. This project aims to address the problem of prolonged traffic signal down time by designing a model traffic signal that uses SMS to automatically and instantly report two of the major faults that occur with traffic signals, that is physical damage and lights failure. For detection of physical damage it uses an accelerometer embedded at a fixed position inside the hollow structure of the pole. It uses the concept that an installed traffic signal will have its pole in a fixed position, and when it is hit by a vehicle in the case of an accident, it moves from the upright position and the accelerometer will detect this motion and registers it to the microcontroller which will then send a signal to the GSM module to send an SMS to the responsible personnel. For detection of light failure it uses a current sensor that is connected to detect the current flowing in the light bulb. When the current is detected to be below a set threshold it registers this to the microcontroller which will then send a signal to the GSM module to send an SMS. For the sake of demonstration of concept, the model was simplified to use one light bulb that has no ON and OFF timings.